Art Deco in Serbian Architecture / Milan Prosen - Alfirević, Đorđe (Arhitektura i urbanizam, 2024)
The monograph Art Deco in Serbian Architecture by Milan Prosen is a monumental historiographical work that thoroughly explores the previously insufficiently researched topic of the presence and influence of Art Deco on interwar architecture, as well as the reasons for its emergence, stylistic characteristics, prevalence, and representation in Serbia. Within a broad framework, the monograph covers and presents topics such as the significance of the term and the emergence of Art Deco worldwide, the social circumstances in which the style originated and was recognized globally, the circumstances in which Art Deco appeared in Serbia, and the specificities of its appearance in Serbian architecture. Dr. Milan Prosen conducted his comprehensive scientific research and completed it during the preparation of his doctoral dissertation, defended at the Faculty of Philosophy, University of Belgrade in 2014, before a respectable committee consisting of Dr. Aleksandar Kadijević, Dr. Mirjana Roter-Blagojević, Dr. Aleksandar Ignjatović, and Dr. Simona Čupić, confirming the value and importance of his work. Since then, the content of the monograph has been supplemented and partially revised, with the text expanded based on new research, including published historiographical knowledge and the author's results related to this topic from previous years.
Keywords: ar deco; architecture; monograph